The Model of Digital Communication and Supply Chain Service for Tourism Industry - Priatna, Deden Komar; Roswinna, Winna; Limakrisna, Nandan (International Journal of Supply Chain Management, 2021)
This study aims to analyze the influence of digital communication, the supply chain service, on visiting decisions through interest in visiting Indonesian tourism. The quantitative approach is used in this research by applying a descriptive design and verification. The sample used was 400 respondents who were Indonesian visitors and social media users. The sampling technique is based on probability sampling technique using random sampling method. Analysis of research data using the method of Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of the study found that digital communication and supply chain service had a significant and positive effect on visiting interest which was shown positively. Interest in visiting has a positive and significant effect on visiting decisions positively.